Profil Keterampilan Abad 21: Survei Persepsi Diri pada Mahasiswa di Timur Kalimantan Barat - Burhanudin Rais; Lailatus Sa'adah; Luthfi Awwalia (LPPM Institut Pendidikan Nusantara Global, 2026)
21st-century skills are essential because supporting various needs, including in the workplace and in society. However, many college graduates currently lack 21st-century skills. This can impact graduates' ability to face the challenges of this era. Similar research conducted in Sintang revealed data at the school level and discussed parts of 21st-century skills, such as critical thinking skills. Consequently, universities are at risk of not preparing learning that is appropriate to the needs of the times, which is feared to impact graduate competency gaps. This study followed the working principles of descriptive quantitative research methods, with a data collection instrument in the form of a questionnaire. This study was completed by students from three different districts: Sintang, Kapuas Hulu, and Melawi, with a sample size of 374 respondents. The results, researchers found that, in general, students' abilities were at a moderate level in all three aspects measured: Information, Media, and Technology Skills received the highest score, and Learning and Innovation Skills. However, upon closer examination, the Creative Thinking component, which is part of the Creativity and Innovation sub-aspect within the Learning and Innovation Skills aspect, was in the low category compared to the other components.